2005
DOI: 10.1177/039139880502800213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapamycin on the Epithelial-to-mesenchymal Transition of Human Peritoneal Mesothelial Cells

Abstract: The preservation of the peritoneal membrane is crucial for long-term survival in peritoneal dialysis. Epithelial-to-mesenchymal transition (EMT) is a process demonstrated in mesothelial cells (MC), responsible for negative peritoneal changes and directly related to PD. EMT enables neovascularization and fibrogenic capabilities in MC. Vascular endothelial growth factor (VEGF) is the mediator for neo-vascularization. Rapamycin is a potent immunosuppressor with antifibrotic action in renal allografts and has a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 24 publications
5
48
2
Order By: Relevance
“…We specifically analyzed the E-cadherin, a-SMA, fibronectin, and collagen I expressions, which are the representative markers implicated in EMT. A little different from Aguilera's study [24], rapamycin showed a remarkable protective effect on HG-induced EMT of RPMCs, as it increased E-cadherin expression and decreased a-SMA, fibronectin, and collagen I expressions. The acquisition of migratory capacity is another typical characteristic of cells undergoing EMT [13].…”
contrasting
confidence: 74%
See 3 more Smart Citations
“…We specifically analyzed the E-cadherin, a-SMA, fibronectin, and collagen I expressions, which are the representative markers implicated in EMT. A little different from Aguilera's study [24], rapamycin showed a remarkable protective effect on HG-induced EMT of RPMCs, as it increased E-cadherin expression and decreased a-SMA, fibronectin, and collagen I expressions. The acquisition of migratory capacity is another typical characteristic of cells undergoing EMT [13].…”
contrasting
confidence: 74%
“…The concentration of HG and rapamycin were used according to our premier data and previous studies [9,24,35]. As shown in Fig.…”
Section: Rapamycin Reverses Hg-induced Emt Of Rat Peritoneal Mesothelmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in this field, using animal models, has examined the efficacy of treatment with ACE (angiotensinconverting enzyme) inhibitors, angiotensin receptor blockers (ARBs), octreotide and corticosteroids on peritoneal alterations that are induced by hypertonic PD solutions (36)(37)(38). There are very limited studies, no matter experimental or clinical, that attempt to investigate and report the effects of MMF and RAP in fibrotic diseases (25,26,30,39,40). Besides, previous work in this field has so managed to produce little direct evidence that would suggest additional biocompatible dialysis solutions can preserve peritoneal function.…”
Section: Discussionmentioning
confidence: 99%